Challenges in Supervising Sharia Banking to Ensure Compliance with Sharia Principles - Maisarah, Aisyah; Muliza, Muliza; Murlisa, Lia (LPPM Institut Pendidikan Nusantara Global, 2025)
Supervision in Islamic banking is a fundamental aspect to ensure that operational activities comply with sharia principles. However, despite the rapid development of Islamic financial institutions, various challenges still hinder comprehensive sharia compliance. This study aims to analyse the challenges of supervision in Islamic banking, particularly regarding the competence of the Sharia Supervisory Board (SSB), institutional independence, effectiveness of the supervisory system, and regulatory disharmony between OJK (Financial Services Authority) and DSN-MUI (National Sharia Council). The research employs a qualitative descriptive approach through library research, using content analysis and thematic analysis methods on various academic literatures and official documents published within the last five years. The findings reveal that the SSB still faces limitations in both expertise and strategic roles, supervision tends to be administrative in nature, and there is a lack of regulatory harmonization aligned with sharia objectives (Maqashid Syariah) and global standards. Therefore, sharia supervision reform should be directed towards strengthening competence, restructuring the SSB’s authority, and integrating both national and international standards into the Islamic banking governance system in Indonesia.